Pembentukan Karakter Kristiani melalui Pendidikan Holistik di Sekolah Katolik - Yusril Firdaus; Geraldy Calvin; Febri Kurniawan (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2024)
This article discusses holistic education in Catholic schools as a means of forming Christian character. Holistic education integrates spiritual, moral, intellectual, and social dimensions to build a whole person according to the values ​​of the Gospel. Case studies in several Catholic schools show that holistic education encourages students to actively participate in church and community life. This article also discusses challenges in its implementation, such as differences in student backgrounds, and strategies to overcome them.